Essential oils and their active components applied as: free, encapsulated and in hurdle technology to fight microbial contaminations. A review. Issue 12 (December 2022) - Yammine, Jina; Chihib, Nour-Eddine; Gharsallaoui, Adem; Dumas, Emilie; Ismail, Ali; Karam, Layal
Abstract: Microbial contaminations are responsible for many chronic, healthcare, persistent microbial infections and illnesses in the food sector, therefore their control is an important public health challenge. Over the past few years, essential oils (EOs) have emerged as interesting alternatives to synthetic antimicrobials as they are biodegradable, extracted from natural sources and potent antimicrobials. Through their multiple mechanisms of actions and target sites, no microbial resistance has been developed against them till present. Although extensive documentation has been reported on the antimicrobial activity of EOs, comparisons between the use of whole EOs or their active components alone for an antimicrobial treatment are less abundant. It is also essential to have a good knowledge about EOs to be used as alternatives to the conventional antimicrobial products such as chemical disinfectants. Moreover, it is important to focus not only on planktonic vegetative microorganisms, but to study also the effect on more resistant forms like spores and biofilms. The present article reviews the current knowledge on the mechanisms of antimicrobial activities of EOs and their active components on microorganisms in different forms. Additionally, in this review, the ultimate advantages of encapsulating EOs or combining them with other hurdles for enhanced antimicrobial treatments are discussed. Abstract : Essential oils; Antimicrobial activity; Encapsulation; Hurdle technology; Disinfection.